Towards UNAIDS 90-90-90 HIV targets: determinants of knowing one’s HIV status in South Africa in 2012 - Agyekum, Mary Pomaa (My University, 2021)
Abstract This study, a secondary data analysis of a national population-based survey, aimed to estimate the proportions of HIV infected people aged 15 years and older who were aware of their HIV status and were exposed to ART. It also sought to determine the factors associated with awareness of HIV status and willingness to provide a blood sample for an HIV test among individuals aged 15 years and older in South Africa. Data for this analysis was from the 2012 South Africa national HIV prevalence, incidence, behaviour, and communication survey (SABSSM). Survey-weighted multinomial logistic regression models were fitted, and adjusted predicted probabilities were used to interpret the association between explanatory variables and outcomes. Out of 26,807 individuals who participated in the study, a weighted percentage of 12.2% people were infected with HIV. Among the people infected with HIV, a weighted 73.9% were aware of their HIV status, and 36% were exposed to ART. In the study population, a weighted 9.5% were unaware of their HIV status and refused an HIV test, 29.9% were unaware of their HIV status and agreed to test for HIV, 14.0% were aware of their HIV status and refused an HIV test, and 46.6% were aware of their HIV status and agreed to test for HIV. Education level, employment status, engagements in HIV related activities, attitude towards HIV infected people and frequency in the use of health services were significant predictors of awareness of HIV status and willingness to provide a blood sample for an HIV test, by adjusting for agegroup, sex, race, geotype and province. The study suggests that almost three out of every four HIV infected people were aware of their HIV status, and 36% were on ART before the UNAIDS 90 90 90 targets were set. This study affirms that engaging in HIV related activities and a positive attitude towards people living with HIV could increase HIV testing, thereby increasing awareness of HIV status.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of MSc in Epidemiology (Biostatistics), October 2021